(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This article aimed to study: (1) the interaction between female users and healing-themed products and how to convey emotions, (2) the evaluation of the interactivity of healing-themed products using the interaction types proposed by Rafaeli and Sudweeks, and (3) the design and evaluation of four types of healing-themed products aimed at conveying a sense of care.The sample consisted of female consumers within a specific age range, selected using a simple random sampling method. Data was collected through structured questionnaires and situational storytelling, and analyzed using descriptive statistics and content analysis. Research findings were as follows: • The wave of healing-themed products originating from Japan can fill the void and loneliness created by societal pressures. • Noddings’ theory of care was applied to the interactive design of healing-themed products, enabling the conveyance of emotions. • The four types of healing-themed products developed received positive reviews from participants, proving that products can serve as a medium for emotional communication.